A review on multilingual voice-to-voice translation. - Ambadekar, Sarita; Dhokiya, Trushil; Gandhi, Hitanshu; Haria, Ishita (Journal of the All India Institute of Speech & Hearing)
Purpose: Real-time multilingual voice-to-voice translation is required to overcome linguistic and cultural barriers as a result of the new prospects for worldwide communication brought about by the rapid growth of technology. The purpose of this research is to examine the fundamental technologies that make this possible, emphasizing their advantages, disadvantages, and complementary roles in promoting intercultural communication. Methods: Three important technologies—Text-to-Speech (TTS), Neural Machine Translation (NMT), and Automatic Speech Recognition (ASR)—are thoroughly reviewed and compared in this paper. TTS produces speech that sounds natural in the target language, NMT translates the text into the target language, and ASR turns spoken language into text. In addition, the examination looks at current developments including transformer-based ASR models, multilingual and adaptive NMT architectures, and non-autoregressive TTS systems such as FastSpeech, FastPitch, and FairSeq. Furthermore, the potential of voice cloning to improve emotional expressiveness and individuality is examined. Results: Recent innovations in these technologies have led to significant improvements in translation speed, accuracy, and naturalness of spoken output. Transformer-based models and multilingual NMT architectures have enhanced translation quality, while non-autoregressive TTS systems have reduced latency and improved speech synthesis. Voice cloning further augments personalization by preserving emotional context and speaker identity. Discussion: The integration of ASR, NMT, and TTS holds tremendous potential to revolutionize real-time multilingual communication, facilitating smoother collaboration, travel, and cultural exchange worldwide. However, challenges remain, including handling low-resource languages, maintaining contextual accuracy, and ensuring emotional fidelity in voice cloning. By addressing these limitations, future advancements could further enhance the effectiveness of multilingual voice translation systems.